2014
DOI: 10.14302/issn.2324-7339.jcrhap-13-191
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning In Adults Aging With HIV: A Cross-Sectional Analysis Of Cognitive Subtypes And Influential Factors

Abstract: Objective This cross-sectional study examined cognitive subtypes and influential factors in HIV-positive (HIV+) adults. Method Two-step cluster analysis was conducted on a neurocognitive test battery in a sample (N = 78) of adults and older adults with HIV (Mage = 46.1). Next, cognitive, functional, and mental and physical health differences were compared between the HIV+ clusters and an HIV- reference group (N = 84; Mage = 47.9). Results A two-cluster solution emerged, with a lower performing cluster exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 22 publications
1
21
1
1
Order By: Relevance
“…Older HIV+ adults (>50 years) in the Hawaii Ageing Cohort were twice as likely as their younger HIV+ counterparts to have HAD after adjusting for other known dementia risk factors 31,32 . Older age has also been associated with increased risk of HAND in several South African cohorts 33,34 ; however, the effect of age on HAND risk is likely confounded by the increased prevalence of cerebrovascular risk factors at older ages 26,35 .…”
Section: Clinical Features Of Handmentioning
confidence: 96%
“…Older HIV+ adults (>50 years) in the Hawaii Ageing Cohort were twice as likely as their younger HIV+ counterparts to have HAD after adjusting for other known dementia risk factors 31,32 . Older age has also been associated with increased risk of HAND in several South African cohorts 33,34 ; however, the effect of age on HAND risk is likely confounded by the increased prevalence of cerebrovascular risk factors at older ages 26,35 .…”
Section: Clinical Features Of Handmentioning
confidence: 96%
“…In a recent cluster analytic study of adults with HIV ( N = 78; M age = 46.61), Fazeli and colleagues (under review) found that a majority of the sample (59%) was classified as neurocognitively “normal” compared to a demographically similar HIV-negative reference group ( N = 84; M age = 47.93). Age was the most influential correlate of cluster membership (“normal” cluster versus lower performing cluster).…”
Section: Hiv and Cognitionmentioning
confidence: 99%
“…Despite viro-immunological efficacy of cART, milder forms of HIV-associated neurocognitive disorders (HAND) still persist (Heaton et al, 2011; Clifford, 2008). The frequency of cognitive symptoms is substantially higher among older PLWH, a population that is rapidly growing due to widespread use of cART (Fazeli, 2015; Justice et al, 2010; Valcour et al, 2004). …”
Section: Introductionmentioning
confidence: 99%